Projections, Birkhoff Orthogonality and Angles in Normed Spaces (Communications in Mathematical Research, 2021)
Let $X$ be a Minkowski plane, i.e., a real two dimensional normed linear space. We use projections to give a definition of the angle $A_q(x, y)$ betweentwo vectors $x$ and $y$ in $X$, such that $x$ is Birkhoff orthogonal to $y$ if and only if $A_q(x, y) = \frac{π}{2}$. Some other properties of this angle are also discussed.
Keywords: projection; norm; Birkhoff orthogonality; angle; Minkowski plane; duality.